2012
DOI: 10.17221/61/2011-pps
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of selected apple cultivars to wilt pathogen Verticillium dahlia

Abstract: Karajeh M.R., Owais S.J. (2012): Reaction of selected apple cultivars to wilt pathogen Verticillium dahlia. Plant Protect Sci., 48: 99-104.The reaction of five apple cultivars to olive wilt caused by Verticillium dahliae Kleb was evaluated. Five apple cultivars (Royal Gala, Delicious Anabri, Double Red, Golden Delicious, Granny Smith) and one olive cultivar (Nabali Mohassan) were inoculated with V. dahliae and grown under partially controlled greenhouse conditions. Typical symptoms of the disease were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Other studies suggest the replacement of wilted olive trees with apple trees, a non-host plant, as an environmentally friendly management practice (Karajeh and Owais, 2012), but little is known about replacement using resistant cultivars of olive. Generally, the rate of Verticillium-dead olive trees per year was 5.59%, when the susceptible cv.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest the replacement of wilted olive trees with apple trees, a non-host plant, as an environmentally friendly management practice (Karajeh and Owais, 2012), but little is known about replacement using resistant cultivars of olive. Generally, the rate of Verticillium-dead olive trees per year was 5.59%, when the susceptible cv.…”
Section: Discussionmentioning
confidence: 99%
“…Replacement of diseased trees with non-host plants might also be an environmentally friendly management solution to control Verticillium wilt. Studies on replacement of dead or severely diseased olive trees with apple trees revealed that this would be an appropriate approach in an integrated disease management to control Verticillium wilt disease (Karajeh and Owais 2012). Use of biological control agents, including beneficial bacteria is another approach to manage Verticillium wilts (Markakis et al 2015;Mercado-Blanco et al 2004;Prieto et al 2009).…”
Section: Management Of the Diseasementioning
confidence: 99%